Microbiological evaluation of LOCATOR® Legacy attachments: A cross‐sectional clinical study. Issue 5 (18th July 2019) - Nagy, Ursina; Guédat, Christophe; Giannopoulou, Catherine; Schimmel, Martin; Müller, Frauke; Srinivasan, Murali
Abstract: Objective: This retrospective cross‐sectional study aimed to evaluate quantitatively the oral microbiome in the tri‐lobe central cavity of Locator Legacy attachment and verify whether it harbors a different, potentially more pathogenic, bacterial spectrum than the adjacent edentulous ridge. Materials and Methods: Edentulous patients rehabilitated with implant overdentures using Locator Legacy attachments were recruited for this study. The clinical examination comprised probing depths, mobility, peri‐implant, and periodontal health along with intraoral swabs for microbiological evaluation, polymerase chain reaction (PCR) testing, and candida culture. The swabs were collected from the trilobed cavity of the attachment and the adjacent edentulous ridge. PCR was performed to detect six specific bacteria, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Tannerella forsythia, Treponema denticola, Prevotella intermedia, and Parvimonas micra . Statistical analyses were performed using McNemar's test and Wilcoxon's rank sum test with the significance set to p < .05. Results: A total of 50 participants with a mean age of 71.5 ± 9.6 years participated in the study. No significant differences in the microbiome were found between samples from the ridge and the attachment. No significantly different numbers in the candida cultures were identified, and the presence of a removable prostheses did not demonstrate a significant association with the prevalence of candida. Conclusions: Within the limits of this study and the investigated bacterial species, the trilobed cavity of the attachment does not seem to increase the bacterial load.